A novel RNA sequencing‐based miRNA signature predicts with recurrence and outcome of hepatocellular carcinoma. Issue 7 (21st May 2018) - Bai, Fumao; Zhou, Huaibin; Ma, Mengni; Guan, Chen; Lyu, Jianxin; Meng, Qing H.
Abstract : Hepatocellular carcinoma (HCC) is the fifth most common type of cancer and the second leading cause of cancer‐related deaths worldwide. Given that the rate of HCC recurrence 5 years after liver resection is as high as 70%, patient with HCC typically has a poor outcome. A biomarker or set of biomarkers that could predict disease recurrence would have a substantial clinical impact, allowing earlier detection of recurrence and more effective treatment. With the aim of identifying a new microRNA (miRNA) signature associated with HCC recurrence, we analyzed data on 306 patients with HCC for whom both miRNA expression profiles and complete clinical information were available from The Cancer Genome Atlas database. Through this analysis, we identified a six‐miRNA signature that could effectively predict patients' recurrence risk; the high‐risk and low‐risk groups had significantly different recurrence‐free survival rates. Time‐dependent receiver operating characteristic analysis indicated that this signature had a good predictive performance. Multivariable Cox regression and stratified analyses demonstrated that the six‐miRNA signature was independent of other clinical features. Functional enrichment analysis of the gene targets of the six prognostic miRNA indicated enrichment mainly in cancer‐related pathways and important cell biological processes. Our results support use of this six‐miRNA signature as an independent factor for predicting recurrence and outcome of patients with HCC. Abstract : The purpose of our research was to identify miRNAs that might serve as reliable biomarkers of hepatocellular carcinoma (HCC) recurrence. In this study, we have established a novel six‐miRNA signature that could effectively stratify risk of recurrence among patients with HCC.